The Influence of E-commerce and Social Media Adoption in Improving the Competitiveness of MSME Products (Proceeding of the International Conference on Economics, Accounting, and Taxation, 2024)
This study aims to analyze the role of digitalization through e-commerce and social media marketing in improving the competitiveness of fashion sector MSMEs in the Industrial Age 4.0. This study uses a descriptive quantitative method with data collection through questionnaires from 33 MSMEs that have utilized digital platforms. The results showed that social media marketing has a significant influence on MSME competitiveness (p = 0.028), while e-commerce did not show a significant influence (p = 0.601). These findings highlight the importance of optimizing social media marketing in creating customer loyalty and increasing brand awareness, although e-commerce still faces barriers such as technological literacy and infrastructure limitations. This research makes a practical contribution by recommending digital skills training and infrastructure support to maximize the potential of digitalization for MSMEs. In addition, the theoretical implications of this study open up opportunities for the exploration of other variables, such as product innovation and business networks, to improve MSME competitiveness more comprehensively.